Relationship between Screen Time and Emotional Well-Being of University Athletes - Raza, Hassan; Bibi, Aisma (JCTE, 2026)
Screen time has become a normal activity at university level and students, even athletes, are spending more time on screen than any other activity when they are on campus. Time spent in front of screens may relate with students’ emotional wellbeing in a positive or negative way. Therefore, this study focused to determine the relationship between screen time and emotional well-being among University athletes overall and also gender wise. A quantitative research with correlational design was carried out to investigate the relationships. The population for this study consisted of registered athletes (216) at Hazara University, Mansehra. The entire population was selected as the sample for the study by using census sampling technique. Two questionnaires, one related to screen time and the other to measure emotional well-being were used. The reliability of both these instruments was .86. Data were collected through online mode and were analyzed through Pearson correlations. The results showed that there was an overall negative relationship between screen time and emotional well-being of Hazara university athletes. Interestingly, the relationship between screen time and emotional well-being was positive among male athletes, while it was negative among female athletes. It is recommended that female student-athletes at university level should be counseled to reflect on their habits of using screen because it’s linked to their emotional wellbeing in a negative way. It should also be explored why is more time spent on screen is helpful for emotional wellbeing of male student-athletes.